The Alcott Sisters in Rome: A Tragicomic Chronicle - Daniela Daniele (European Journal of American Studies)
This article recounts the Alcott sisters’ experience in Rome, in the contingency of the Tiber’s flood and of the political transition to the Italian unification. The arrival of the King of Italy is welcomed by Louisa May and originates, along with the inundation, a vivid urban sketch written in the tragicomic style of Dickens. Alcott’s support to the patriots is here discussed as part of the neglected intellectual legacy of Bronson Alcott, whose romantic pedagogy inspired Little Men: her novel conceived and written in Rome.